1997
DOI: 10.5271/sjweh.269
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence of sulfite pulp workers in Denmark

Abstract: The following articles refer to this text: 2001;27(2):0; 2002;28(5):0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Earlier investigations among pulp and paper workers (7,30) and wood workers (3 1) all concluded that the increased risk for lung cancer could not be explained by smoking alone. We observed the highest risk among sulfite mill workers, a finding in agreement with that of other reports (3,32). Sulfur dioxide is a major air contaminant in sulfite mills, and nearly all process workers involved in cooking, washing, and other operations are exposed to this chemical.…”
Section: Discussionsupporting
confidence: 82%
“…Earlier investigations among pulp and paper workers (7,30) and wood workers (3 1) all concluded that the increased risk for lung cancer could not be explained by smoking alone. We observed the highest risk among sulfite mill workers, a finding in agreement with that of other reports (3,32). Sulfur dioxide is a major air contaminant in sulfite mills, and nearly all process workers involved in cooking, washing, and other operations are exposed to this chemical.…”
Section: Discussionsupporting
confidence: 82%
“…Risk factors for skin melanoma are mainly related to skin constitution, intermittent sun exposure, and the propensity to sunburn (28); controlling for these factors was not possible in our study. Evidence for occupational risk factors in the pulp and paper industry was not documented for skin melanoma in a large case-referent study with exposure assessment (29), nor reported in cancer incidence studies carried out in this industry (15)(16)(17). The incidence rates of both prostate cancer and skin melanoma in British Columbia are significantly increased when compared with Canadian rates (21); thereby the possibility of an overestimated risk in our study is raised.…”
Section: Discussionmentioning
confidence: 64%
“…The association with rectal cancer among the long-term workers in the sulfite process was difficult to interpret. Such a relationship has been reported in a mortality study (4), but in none of the incidence studies (15)(16)(17). The excess risk for pleural cancer probably represents past asbestos exposure (1,23), since all except 1 of the 10 cases were mesotheliomas.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…All workers employed in 1960, 1970 or both years in pulp mills (N=28 142, industrial codes 260 and 261) and paper mills (N=39 169, industrial codes 262 and 264, including the paper packaging industry), as well as different occupations in pulp and paper mills were compared with all gainfully employed Swedish men. Occupational codes for the workers in pulp and paper mills were combined and analyzed according to worktasks: chemical process workers (occupational codes 830-839); maintenance workers, broadly defined (occupational codes 700-799), "chemistry workers"; mostly chemistry technicians working in process operations (occupational codes 4,11,14); and "packers", paper product workers and packers (occupational codes 857, 881). Single occupational codes with more than three cases were also analyzed and reported.…”
Section: Methodsmentioning
confidence: 99%